BD-02 Blockade of the mechanistic target of rapamycin elicits rapid and lasting improvement of disease activity through restraining pro-inflammatory T cell lineage specification in patients with active SLE. (August 2018) - Lai, Zhi-Wei; Kelly, Ryan; Winans, Thomas; Marchena, Ivan; Shadakshari, Ashwini; Yu, Julie; Dawood, Maha; Garcia, Ricardo; Tily, Hajra; Francis, Lisa; Faraone, Stephen V; Phillips, Paul E; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) patients exhibit T-cell dysfunction that has been attributed to mechanistic target of rapamycin activation. Therefore, safety, tolerance, and efficacy of rapamycin were examined in a prospective biomarker-driven open-label clinical trial. Methods: 40 patients having active disease and unresponsive or intolerant to conventional medications were enrolled. Sirolimus was started at 2 mg/day with dosage adjusted to tolerance and 6–15 ng/ml trough levels. Disease activity was evaluated by BILAG, SLEDAI, and prednisone use over 12 months. Blood samples of 56 matched healthy subjects were obtained as controls for immunometabolic outcomes monitored at each visit. Results: 11 patients dropped out, 9 for non-compliance and 2 for intolerance. Among safety outcomes, liver function and lymphocyte counts were unchanged. While HDL-cholesterol, neutrophil counts and haemoglobin were moderately reduced, all changes occurred within a range considered safe. Platelet counts were slightly elevated over 12 months. As primary clinical efficacy endpoint, SLEDAI and BILAG disease activity scores were reduced over 12 months in 16/29 patients (55%). 19/29 patients (65.5%) met criteria for SLE Responder Index (SRI). Arthritis, rash, pyuria, and hypocomplementemia improved among SLEDAI components, while cardiopulmonary, musculoskeletal, mucocutaneous, and vasculitis BILAG organ-domain scores also declined. Prednisone use diminished from 24.3±4.7 mg/day to 7.2±2.3 mg/day (p<0.0009). Sirolimus expanded CD4 + CD25 + FoxP3 + Tregs and CD8 + memory T cells and inhibited IL-4 and IL-17 production by CD4 + and CD4 - CD8 - double-negative T cells after 12 months. CD8 + memory T cells were selectively expanded in SRI-responders. Conclusions: Sirolimus elicits rapid, progressive, and sustained improvement of disease activity by correcting pro-inflammatory T-cell lineage specification in patients with active SLE. Acknowledgements: This work was supported in part by an Investigator-Initiated Research Grant P0468 × 1–4470/WS1234172 from Pfizer and grants AI 048079, AI 072648, and AI 122176 from the National Institutes of Health and the Central New York Community Foundation. Trial registration: Prospective Study of Rapamycin for the Treatment of SLE; ClinicalTrials.gov Identifier: NCT00779194 . Treatment trial of SLE with N–acetylcysteine; ClinicalTrials.gov identifier: NCT00775476 . References: . Perl A. Mechanistic target of rapamycin pathway activation in rheumatic diseases. Nat. Rev. Rheumatol. 2016;12:169–82. . Yoshida S, et al. Redox regulates mammalian Target of Rapamycin Complex 1 (mTORC1) activity by modulating the TSC1/TSC2-Rheb GTPase pathway. J. Biol. Chem 2011;286:32651–60. . Lai Z-W, et al. N-acetylcysteine reduces disease activity by blocking mTOR in T cells of lupus patients. Arthritis Rheum2012;64:2937–46. . Perl A, et al. Comprehensive metabolome analyses reveal N-acetylcysteine-responsive accumulation of kynurenine in systemic lupus erythematosus: Implications for activation of the mechanistic target of rapamycin. Metabolomics2015;11:1157–74. . Lai Z, et al. Sirolimus in patients with clinically active systemic lupus erythematosus resistant to, or intolerant of, conventional medications: A single-arm, open-label, phase 1/2 trial. Lancet2018;391:1186–96.